Going the Extra Mile: Why Clinical Research in Cystic Fibrosis Must Include Children - Rebecca Dobra; Siân Bentley; Claire Edmondson; Maxine Ovens; Clare Saunders; Christopher Short; Gemma Wilson; Jane C. Davies; Andrew Bush (MDPI AG, 2022)
This is an exciting time for research and novel drug development in cystic fibrosis. However, rarely has the adage, "Children are not just little adults" been more relevant. This article is divided into two main sections. In the first, we explore why it is important to involve children in research. We discuss the potential benefits of understanding a disease and its treatment in children, and we highlight that children have the same legal and ethical right to evidence-based therapy as adults. Additionally, we discuss why extrapolation from adults may be inappropriate, for example, medication pharmacokinetics may be different in children, and there may be unpredictable adverse effects. In the second part, we discuss how to involve children and their families in research. We outline the importance and the complexities of selecting appropriate outcome measures, and we discuss the role co-design may have in improving the involvement of children. We highlight the importance of appropriate staffing and resourcing, and we outline some of the common challenges and possible solutions, including practical tips on obtaining consent/assent in children and adolescents. We conclude that it is unethical to simply rely on extrapolation from adult studies because research in young children is challenging and that research should be seen as a normal part of the paediatric therapeutic journey.